2006
DOI: 10.1002/cyto.a.20300
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of two caspase activities simultaneously in living cells by a novel dual FRET fluorescent indicator probe

Abstract: Background: A number of fluorescent caspase substrates and FRET-based indicators have been developed to study the in vivo activation of caspases, a conserved family of proteases critical in inflammatory, and apoptosis signaling pathways. To date, all substrates have measured only one caspase activity. Here, we describe a FRET-based probe for simultaneously measuring two distinct caspase activities in living cells. Methods: This probe consists of a CFP-YFP-mRFP fusion protein containing a caspase-3-cleavage mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
45
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 53 publications
1
45
0
Order By: Relevance
“…We showed that not only sialic acids, but also fucose, could be successfully used for FRET detection. These findings open up the possibility of further applications of this FRET technique, such as simultaneous detection of different glycoforms on the same protein using, for example, a double FRET technique to detect two FRET pairs sharing one fluorophore [37][38][39] .…”
Section: Discussionmentioning
confidence: 95%
“…We showed that not only sialic acids, but also fucose, could be successfully used for FRET detection. These findings open up the possibility of further applications of this FRET technique, such as simultaneous detection of different glycoforms on the same protein using, for example, a double FRET technique to detect two FRET pairs sharing one fluorophore [37][38][39] .…”
Section: Discussionmentioning
confidence: 95%
“…Although caspase-3 and -7 are structurally similar and can be inhibited by Z-VAD-FMK, caspase-6 shows very different characteristics and cannot be inhibited by Z-VAD-FMK (33). In addition, caspase-6 is activated by both caspase-3-dependent and -independent cascades (36). Moreover, FAM-DEVD-FMK used for measuring caspase-3 activity can also bind to caspase-7 and -6.…”
Section: Discussionmentioning
confidence: 99%
“…These reporters monitor a change in the FRET intensity upon caspase cleavage (13)(14)(15). The multimodality reporter uses copies of the caspase-recognition sequence to link a fluorescent protein, a bioluminescent protein, and a positron emission tomography reporter, which can each be more readily detected after caspase cleavage (16).…”
mentioning
confidence: 99%